Wayward Needle and Familiar Spirit: The Trajectories of Rui and Francisco Faleiro in Early Modern Spain - Collins, Edward (2019)
In this article, I examine the presence and influence of the Faleiro brothers, Rui and Francisco, who accompanied Magellan to Spain in 1518. This article examines the respective contributions of each brother to the expedition itself, as well as their subsequent contributions to the development of nautical science and navigation in sixteenth-century Spain. It examines their recruitment and presence in the context of political division surrounding the recruitment of large numbers of foreigners for Spanish fleets and assesses whether there was a different approach or attitude toward individuals such as the Faleiros who had discernible skills.